Capability of Ketip Banana (Musa paradisiaca Forma typiaca) Peel Ethanol Extract in Reducing Sperm Abnormality Number of Mice (Mus musculus) Following Tobacco Smoke Exposure - Bahri, Syamsul; Setiadi, Dadi; Lestari, Tri Ayu; Ilmi, Muhamad Yazid Mizanul; Saputra, Jagat (Jurnal Biologi Tropis, 2024)
Antioxidants are important in maintaining body health as their ability in binding free radicals and remove cell damaging molecules from the body. Plant-based foods are the best source of antioxidants, may contain secondary metabolite compounds such as flavonoids, phenolic acids, saponin, polyphenols and tannins. Peel of fruits sometime just become a domestic trash and pollute the environment. One of tropical fruit which is contain secondary metabolite with antioxidant properties is Ketip banana. Peel of this fruit just left a trash of domestic pollutant whereas it could be transform to become a more valuable product. The aim of this research is to study the effect of ethanol extract of Ketip banana on sperm morphology. To address this goal we applied ethanol extract of Ketip banana on male mice orally using a gavage needle following tobacco smoke exposure. Data analysis showed that tobacco smoke exposure significantly increase sperm abnormality number, but ethanol extract of Ketip banana significantly reduce sperm abnormality number. It is concluded that ethanol extract of ketip banana capable in reducing sperm abnormality number by dosage dependent manner.